Increase in cases of leishmaniasis after earthquake in an endemic area of Ecuador - Quijije Quijije, Cindy Yuleisy; Rivero-De Rodríguez, Zulbey Chiquinquirá; Posligua-Barcia, Stefanía Monserrate; Arteaga-Quiroz, Miguel Ángel (Kasmera, 2025)
Leishmaniasis is an infectious parasitic disease transmitted by the bite of Phlebotomus; in America, the genus responsible is Lutzomyia. Vector-borne infections can increase significantly in the event of natural disasters. The province of Manabí, in Ecuador, is an endemic area for cutaneous leishmaniasis, but in 2016, following the earthquake, there was an increase in cases that year, which continued into 2017. The parish of Portoviejo with the highest number of cases that year was Andrés de Vera. To identify the factors that contributed to this increase, an observational, descriptive, bispective, and cross-sectional study was designed, and a survey was conducted of 383 individuals in the parish of Andrés de Vera, Portoviejo canton, Manabí. There was a high level of ignorance about the vector and few protective measures in homes, such as the use of window screens, mosquito nets, or repellents. It was concluded that the increase in cases could be due to the harsh weather conditions experienced by many residents after the earthquake and a lack of knowledge about protective measures, considering that the area evaluated is defined as endemic for leishmaniasis